Ответы и объяснения

2013-01-23T18:24:49+00:00

 б)

log^{2}_{3}(x-1)-2log_{\frac{1}{3}}=2^{log_{2}7}

log^{2}_{3}(x-1)+log_{3}\frac{81}{(x-1)^{2}}=7

log^{2}_{3}(x-1)+log_{3}81(x-1)^{-2}=7 

log^{2}_{3}(x-1)+log_{3}81+log_{3}(x-1)^{-2}=7 

log^{2}_{3}(x-1)-2log_{3}(x-1)-3=0 

log_{3}(x-1)=t

t^{2}-2t-3=0 

t_{1}=3

t_{2}=-1 

log_{3}(x-1)=3

x-1=3^{3}

x-1=27

x_{1}=28 

log_{3}(x-1)=-1

x-1=3^{-1}

x_{2}=1\frac{1}{3}

 а)

log_{7}x+log_{49}36=log_{\frac{1}{7}}(2x+6)+log_{7}48

log_{7}x+log_{7}6=-log_{7}(2x+6)+log_{7}48 

log_{7}6x=-log_{7}(\frac{48}{2x+6}) 

6x=\frac{48}{2x+6} 

6x(2x+6)=48 

12x^{2}+36x-48=0 

x^{2}+3x-4=0 

x_{1}=1 

x_{2}=-4

б)

log^{2}_{2}(4-x)+log_{\frac{1}{2}}\frac{8}{4-x}=2^{log_{4}9})

log^{2}_{2}(4-x)-log_{2}8+log_{2}(4-x)=3 

log^{2}_{2}(4-x)+log_{2}(4-x)-6=0

log_{2}(4-x)=t 

t^{2}+t-6=0

 

t_{1}=2 

 

t_{2}=-3 

 

log_{2}(4-x)=2 

 

 

 

4-x=4 

x_{1}=0 

log_{2}(4-x)=-3 

4-x=\frac{1}{8}

 

x=3\frac{7}{8}